Improving Speaking Skills through the Storytelling Method for Fifth Grade Students at SD Negeri 8 Seram Timur - Firda Bugis; Sarah Sahetapy; Ribka L. Ririhena (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to improve the speaking skills of fifth-grade students at SD Negeri 8 Seram Timur through the Story Telling learning method. The research design used was Classroom Action Research (CAR) consisting of two cycles including planning, action, observation, and reflection stages. The research subjects were 12 students. Data were collected through tests and observations, and analyzed using descriptive quantitative methods. The results showed an improvement in students’ speaking skills in each cycle. The average pre-test score of 60.96 increased to 65.98 in the first cycle and 80.9 in the second cycle. Therefore, the application of the Story Telling method was proven effective in improving the speaking ability of fifth-grade students at SD Negeri 8 Seram Timur.